MOLECULAR DETECTION OF FUSOBACTERIUM NUCLEATUM IN IN KAZAKHSTANY PATIENTS WITH COLORECTAL CANCER - Kurentay , B.A.; Gusmaulemova , A.D.; Utupov , T.A.; Auganova , D.N.; Tarlykov , P.V.; Khamzina , S.S.; Mamlin , M.A.; Kozhakhmetov , A.M.; Shalekenov , S.B.; Kulmambetova , G.N. (Eurasian Journal of Applied Biotechnology, 2024)
Colorectal cancer is the leading cause of cancer death worldwide. Fusobacterium nucleatum is thought to play an important role in the development of colorectal cancer. F. nucleatum there are many studies that prove that has a great influence on the oncogenesis of colorectal cancer, but the participation of the bacterium in this process remains unclear. The goal of our study is to find out in colorectal cancer tissue F. nucleatum was the definition. Biomaterials from 43 colorectal cancer patients from the National scientific cancer center were analyzed. To detect bacteria, DNA was extracted from the biomaterial and culture inoculation was carried out in parallel. F. nucleatum detection was performed by two methods using Matrix activated laser microbiological desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and quantitative real-time PCR detection. As a result, MALDI determined 14.58%, and qPCR detected 46.51% of bacteria. Thus, F. nucleatum can be a biomarker of colorectal cancer risk.